Marketing and the law - Clarke, Bruce R . (Sydney : LexisNexis, 2006)
Examines the legal controls imposed on the manufacturing, labelling, packaging, distribution, promotion, pricing and retailing of goods and services. The book aims to provide a text appropriate for practitioners and marketing students, and focuses on the impact of the laws on the marketing of products.
CONTENTS : Introduction to the law of marketing -- 2. Protecting inventive ideas -- 3. Protecting commercial secrets -- 4. Protecting copyright material -- 5. Protecting commercial designs -- 6. Trade designations: passing off and unfair trading -- 7. Trade designations: registration of trade marks -- 8. Product packaging and labelling -- 9. Product liability -- 10. Advertising -- 11. Selling techniques and electronic commerce -- 12. Competition law -- 13. Collusive conduct -- 14. Misuse of market power -- 15. Mergers -- 16. Resale price maintenance -- 17. Exclusive dealing -- 18. Franchising.
Previous edition: 2005.
Keywords: Australia; Marketing -- Law and legislation -- Australia; Marketing -- Law and legislation